Up-regulation of IL-12 in monocytes: a fundamental defect in common variable immunodeficiency - Cambronero, R; Sewell, W A; North, M E; Webster, A D; Farrant, J (The Journal of immunology (1950), 2000)
We show that LPS-stimulated circulating CD14-positive monocytes from patients with common variable immunodeficiency (CVID) express a higher proportion of intracellular IL-12-positive cells than monocytes from patients with X-linked agammaglobulinemia or normal subjects. We used four-color flow cytometry and measured IL-12 with an Ab to the p40 subunit following stimulation with LPS. The raised IL-12 is associated with an increased frequency of IFN-gamma-positive T cells, but not of IFN-gamma-positive CD56+ NK cells. These increases in frequency of cytokine-positive cells are due to a decrease in the absolute numbers of circulating monocytes and T cells that are negative for IL-12 and IFN-gamma, respectively. The increased frequency of IL-12-positive monocytes appears to be selective because TNF-alpha was not increased, and is thus unlikely to reflect a general activation. Chronic infection is also unlikely to explain our data since cells from X-linked agammaglobulinemia patients with a similar Ig deficiency do not show these changes. Our data suggest a fundamental abnormality in the IL-12/IFN-gamma circuit in CVID, with up-regulation of IL-12 being the "primary" factor. This imbalance is likely to skew the immune response away from Ab production and also explains the failure of CVID T cells to make Ag-specific memory cells and the chronic inflammatory and granulomatous complications that are a feature of CVID. This disease appears to be a rare example of a polarized Th1-type response and may in part be due to a genetic defect in the control of IL-12 production.